The ethics of clinical research in the era of COVID-19 - Vitti, Juliana N.; Vitti, Robert; Chu, Karen; Mellis, Scott (Frontiers in Public Health, 2024)
There is an urgent need for increased understanding of COVID-19 and strategies for its prevention, treatment, and mitigation. All participants in the research enterprise, including institutional review boards, have an ethical duty to protect participants and ensure that the benefits gained from such research do not conflict with the core principles that guided researchers prior to the pandemic. In this review, we discuss the ethical issues surrounding initiation and conduct of clinical trials, focusing on novel COVID-19 therapeutic, vaccine, or biospecimen research, using the principles of autonomy, beneficence, and justice. We discuss strategies to manage the practical challenges associated with the conduct of clinical trials, with an emphasis on maintaining the rights and welfare of research participants.